The attitudes of neonatologists towards extremely preterm infants: a Q methodological study. Issue 1 (15th July 2015) - Gallagher, Katie; Aladangady, Narendra; Marlow, Neil
Abstract : Objectives: The attitudes and biases of doctors may affect decision making within Neonatal Intensive Care. We studied the attitudes of neonatologists in order to understand how they prioritise different factors contributing to decision making for extremely preterm babies. Design: Twenty-five neonatologists (11 consultants and 14 senior trainees) participated in a Q methodological study about decision making that involved the ranking of 53 statements from agree to disagree in a unimodal shaped grid. Results were explored by person factor analysis using principle component analysis. Results: The model of best fit comprised 23 participants contributing a three-factor model, which represented three different attitudes towards decision making and accounted for 59% of the variance. Fourteen statements were ranked in statistically significant similar positions by 23 participants; consensus statements included placing the baby and family at the centre of care, limitation of intervention based upon perceived risk and non-mandatory intervention at birth. Factor 1 participants (n=12) believed that treatment should not be limited based on gestational age and technology should be used to improve treatment. Five factor 2 participants identified strongly with a limit of 24 weeks for treatment, one of whom being polar opposite, believing in treatment at all costs at all gestations. The remaining six factor 3 participants identified strongly with statements that treatment should be withheld on quality of life grounds. Conclusions: This study has identified differences in attitudes towards decision making between individual neonatologists and trainees that may impact how decisions are communicated to families.